Review of factors which contribute to graduate employees' intention to stay in South Africa - Hart-Davies, Jacqueline (Organisational Psychology, 2016)
In the past decade, human resource practitioners have focused their attention on employee retention. They have tried various practices in order to keep their employees in the organisation for longer. The research gap identified is in the graduate employees' intention to stay context. There has been even less research in this field within South Africa. This study aims to examine the extent to which career advancement opportunities and supervisor involvement contribute to graduate employees' intention to stay. In addition, this study focused on four factors namely, career progression, continuous learning, performance management and recognition in analysing the extent to which these four factors have contributed to graduate employees' intention to stay. Job satisfaction and affective commitment were also examined for their mediational effects on the relationship between career advancement opportunities, supervisor involvement and graduate employees' intention to stay. Graduate employees working in South African organisations participated in a self-report, quantitative survey (N = 357). Whilst the exploratory factor analysis of the intention to stay revealed a unidimensional factor, it was interesting to note that career progression and continuous learning loaded onto one distinct factor, labelled as career advancement opportunities. The multiple regression analysis indicated that career advancement opportunities and supervisor involvement were statistically significant predictors of intention to stay. Process mediation was used to test whether job satisfaction and affective commitment were mediators between career advancement opportunities, supervisor involvement and intention to stay. It was found that both job satisfaction and affective commitment were significant partial mediators in the abovementioned relationship. The study discusses suggestions for future research and the implications, both theoretical and practical, associated with the study.